Pemetaan Pengadaan Dan Optimasi Bahan Baku Batik Sebagai Industri Kreatif Di Kampung Batik Laweyan - Wardani, Indigofera Kusuma, Siti Nandiroh, S.T., M.Eng, Ahmad Kholid Al Ghofari, S.T., M.T (2015)
Surakarta city is known as the city of batik. Where Surakarta establish batik as an icon of their city. Kampung Batik Laweyan has great potential, especially in the field of batik. Not only as one of the biggest batik producers in Surakarta, but Kampung Batik Laweyan as well as tourist areas as well as a means of learning. With its potential and to facilitate SMEs in the face of MEA then necessary to identify the industry's profile in terms of raw materials for the government to participate in improving the potential for international dikanca batik industry. The purpose of this study to determine the profile of batik industry, raw materials, raw material procurement system, the percentage of natural and artificial dyes pengggunaan contained in Kampung Batik Laweyan. The object of this research is an industry that is contained in Kampoeng Batik Laweyan Development Forum which produces from the beginning to the end. The method used to resolve the existing problems is by using descriptive analysis, value chain analysis, linear programming. The results showed that the sustainability of this industry batik industry can be seen from the side of formal education, informal, government support. The type of raw material most widely used are the type of cotton fabric, with natural dyes derived from extracts of the stem, and artificial colorings remasol types. Raw materials procurement system is done routinely, with the scale of purchases as needed. The proposal of value chain analysis that is necessary for the planning and control of raw materials in Kampung Batik Laweyan. Percentage use of natural dyes in Kampung Batik Laweyan by 39% and by 61% artificial coloring.